Fostering AI literacy in pre-service physics teachers: inputs from training and co-variables - Abdulayeva, Aigerim; Zhanatbekova, Nazym; Andasbayev, Yerlan; Boribekova, Farzana (Frontiers in Education, 2025)
BackgroundWhile the transformative potential of artificial intelligence (AI) in education is widely recognized, the rapid evolution of these technologies necessitates a corresponding evolution in teacher education. This research sought to investigate the impact of a targeted training program on pre-service physics teachers’ AI literacy levels and their subsequent attitudes and intentions toward AI adoption in their future teaching.MethodsA pre-post-test control group quasi-experimental study was implemented among physics teacher education students. A 5 weeks long out-of-curriculum intervention was designed and implemented that combined theoretical grounding with practical, problem-based learning activities, with a focus on the use of various AI tools.ResultsThere was a significant upswing in AI literacy performance post-intervention, showcasing that the training was effective in facilitating participants’ understanding and application of AI in educational contexts. Additionally, perceived usefulness of AI was found to be a partial mediator in the link between literacy scores and behavioral intention to embed generative solutions into potential teaching.ConclusionThe study concludes that incorporating comprehensive AI literacy programs into teacher education curricula is essential for fostering a technologically adept and pedagogically innovatively minded teaching workforce. Further research is needed to explore the long-term effects of AI literacy training on teacher practice and student learning outcomes.